THE EFFECT OF AUDIO VISUAL ON THE STUDENTS’ LISTENING COMPREHENSION OF SMP T. P DAYA CIPTA MEDAN - srininta Tarigan; Setilina Bu'ulolo; ifan Giawa; Herman Yanto Gea; Peibe Elisabeth Silaen (elt, 2019)
Abstract This research was aimed to find the effect of audio visual on the students’ listening comprehension of SMP Daya Cipta Medan. This research was conducted by using experimental research design. There were two groups in this research, namely experimental and control group. The data obtained from the score of the experimental class and the control class were analyzed by applying t-test formula and it was found that the students’ score taught by applying audio visual media was higher than the students’ achievement without applying audio visual. It means that the application of audio visual affects students’ listening comprehension. The result of computation of by using t-test is called t-observed. In this study, the result of computation by using t-test is 4,291 and the calculation by using t-test for degree of freedom ( df ) 34 ( Na=Nb-2=19-19-2) at the level of significant 0,05 that critical value is 1,308. The result of computation by using t-test showed observed (t-obs) is higher than t-tabel. It can be seen as follows. T – Obs > t-tabel (t=0.05) with df 19 and 4,291 > 1,308 (t=0,05) with df 19. It means that alternative hypothesis (Ha) is accepted.